Good Governance Practiced By The Malaysian Mosque Committees In Managing Mutual Benevolence: Member’s Perception - Sharifah Norhafiza Syed Ibrahim; Hamidah Bani; Radziah Mahmud; Mohd Yassir Jaaffar; Salina Abdullah; Mohd Tarmizi Ibrahim (USIM Press, 2024)
Vol. 26 No. 2 (2021): Special Edition